Increased adult neurogenesis associated with reactive astrocytosis occurs prior to neuron loss in a mouse model of neurodegenerative disease. (27th September 2017) - Liu, Ting‐Ting; Ye, Xiao‐Lian; Zhang, Jin‐Ping; Yu, Ting‐Ting; Cheng, Shan‐Shan; Zou, Xiao‐Chuan; Xu, Yun; Chen, Gui‐Quan; Yin, Zhen‐Yu
Summary: Aims: This study was to investigate whether cell proliferation and adult neurogenesis are affected at early neurodegenerative stage when neuron loss has not begun to display. Methods and Results: Forebrain‐specific nicastrin ( NCT ) conditional knockout (cKO) mice were generated by crossing NCT f/f with CaMKII α ‐Cre Tg mice. BrdU was used as a lineage tracer to label proliferating neural progenitor cells (NPCs). Immunohistochemistry (IHC) on BrdU indicated that the total number of BrdU positive (+) cells was increased in NCT cKO mice. IHC on doublecortin (DCX) showed that the total number of DCX+ cells was also increased in NCT cKO mice. NCT cKO mice displayed significant astrogliosis as well. However, NCT cKO mice at 3 months did not show significant neuronal death or synaptic loss. Conclusions: NCT‐dependent γ‐secretase activity plays an important role in cell proliferation and immature neuron generation. Enhanced neurogenesis and astrogliosis may be early cellular events prior to the occurrence of neuronal death in neurodegenerative disease.